Tuomas Martikainen: Religion, Migration, Settlement. Reflections on Post-1990 Immigration to Finland - Rimestad, Sebastian (Entangled Religions, 2016)
This contribution offers a review of: Tuomas Martikainen: Religion, Migration, Settlement. Reflections on Post-1990 Immigration to Finland Leiden/Boston: Brill, 2013. 159 pages, € 92,00/ 125.00, ISBN: 978-90-04-24846-5 (hardback), 978-90-04-25058-1 (e-book)